Sensitivity of measuring the progress in financial risk protection to varied survey instruments: A case study of Ghana - Sumboh, Jemima Ambamaah Catherine (Department of Public Health and Family Medicine, 2022)
Valid and reliable data on household health expenditure and other household consumption expenditure are important for monitoring the progress towards Universal Health Coverage (UHC). However, the difficulty in obtaining reliable estimates of private expenditure on health often undermine the credibility of health accounts, limit the tracking of financial resources, and make international comparisons extremely difficult. This study assessed the sensitivity of estimates of out-of-pocket health payments and catastrophic health expenditure to the choice of survey instruments. The study used a household budget survey dataset collected in Ghana, in 2017/2018 by the Navrongo Health Research Center. The health expenditure questions were disaggregated into three different levels: Versions I, II and III containing 11, 44 and 56 health expenditure items, respectively. The number of non-health items and recall periods, however, were held constant across versions. Catastrophic health expenditure was measured as out-of-pocket health expenditure that exceeded a certain fraction of household non-food expenditure, depending on the socioeconomic group. Concentration indices were also used to determine the concentration of catastrophic health expenditure. The mean and median household out-of-pocket health expenditure per annum ranged from US$74.11 to USD$106.49, and US$13.69 to US$20.33, respectively depending on the type of survey instrument used. Also, between 7.98% and 12.68% of households incurred catastrophic out-of-pocket health payments, depending on the survey instrument used. The findings show that estimates of out-of-pocket health spending and financial catastrophe are sensitive to the level of disaggregation of out-of-pocket health spending questions in survey instruments. The concentration indices for catastrophic headcount and overshoot were all negative across all catastrophic threshold levels and data versions implying that catastrophic health payments are concentrated among poor households. Further research is needed, preferably validation studies, to enhance the reliability and comparability of estimates of OOP health expenditure and catastrophic health expenditure.